High prevalence of abdominal aortic aneurysm in older men with cerebrovascular disease: Evaluation of a local screening program - Loban, M.; Gratama, J. W. C.; Klemm, P. L.; Van Leeuwen, Roeland B.; Vriesema, H.; Bienfait, Henri Paul (Frontiers in Neurology, 2023)
INTRODUCTION: Patients with cerebrovascular disease may suffer from other vascular morbidity, such as Abdominal Aortic Aneurysm (AAA). Earlier, a high prevalence of AAA has been demonstrated in men of 60 years of age and older with TIA or stroke. This report evaluates a decade of local screening program for AAA in this selected neurologic population. METHODS: Men of ≥60 years old admitted to the Neurology ward of a community-based hospital in the Netherlands from 2006 through 2017 with a diagnosis TIA or stroke were selected for the screening. The diameter of the abdominal aorta was assessed by abdominal ultrasonography. Patient with detected AAA were referred for evaluation to a vascular surgeon. RESULTS: AAA was detected in 72 (6.9%) of 1035 screened patients. AAAs with a diameter 3.0-3.9 cm accounted for 61.1% of the total found aneurysms, AAAs with a diameter 4.0-5.4 cm for 20.8% and large aneurysms with a diameter ≥5.5 cm for 18.1% of all found aneurysms. Eighteen (1.7%) patients underwent elective aneurysm repair. DISCUSSION: The detection rate of AAA in older men with cerebrovascular disease is roughly fivefold the detection rate in the known European screening programs in older men from general population. Also the proportion of large AAAs (≥5.5cm) is substantially higher. These findings reveal previously unknown co-morbidity in patients with cerebrovascular disease and may be helpful for cardiovascular management in this large group of neurologic patients. Current and future AAA screening programs may also profit from this knowledge.